Pengaruh Budaya Organisasi dan Manajemen Perubahan Terhadap Kinerja Anggota Polres Cilegon Pada Pengamanan Pemilihan Walikota Cilegon Tahun 2024 - Ariztian, Yopi Rizki Ariztian; Earlyanti , Novi Indah; Halimah, Halimah (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyse the influence of organisational culture and public trust on the performance of Cilegon District Police members in securing the 2024 Cilegon Mayoral Election. The main focus of the research is whether organisational culture and the level of public trust can influence the effectiveness of police performance in maintaining neutrality and security during the election process. This study uses organisational culture theory, public trust theory, and performance theory as the basis for analysis. The research method is a quantitative approach with survey techniques, data obtained by distributing questionnaires to 130 respondents in the Cilegon Police jurisdiction. Data processing using Structural Equation Modeling (SEM) method to test the influence between variables. The results showed that organisational culture has a significant effect on public trust and police performance. Public trust is proven to mediate the influence between organisational culture and police performance. This finding shows that the better the organisational culture at Cilegon Police Station, the higher the level of public trust, which also improves police performance in securing elections.